Genetic analysis of Xp22.3 micro-deletions in seventeen families segregating isolated form of X-linked ichthyosis. Issue 3 (December 2015) - Ali, Raja Hussain; Mahmood, Sabba; Raza, Syed Irfan; Aziz, Abdul; Irfanullah,; Naqvi, Syed Kamran-ul-Hassan; Wasif, Naveed; Ansar, Muhammad; Ahmad, Wasim; Shah, Sayed Hajan; Khan, Bakht Tarin; Zaman, Qaiser; et al.
Highlights: We presented the first report of Xp22.3 micro-deletions underlying isolated XLI in seventeen familial cases representing major ethnic groups living in Pakistan. Four distinct micro deletions ∼1.67 Mb, ∼1.62 Mb, ∼1.24 Mb and ∼1.23 Mb were identified in genetic analysis. SNP array fine mapped the breakpoints of two most prevalent micro-deletions at Xp22.3 A rare genetic finding of homozygous micro-deletion in two affected sisters with profound cutaneous scaling.